Knowledge, attitude and practice towards emergency contraceptive pills and factors hindering its use among females of reproductive age group visiting urban health centre at Rajbiraj, Nepal - Chaudhary, Sabina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Unintended pregnancy, unplanned birth and unsafe abortion have been a major challenge to the reproductive health of women worldwide. Despite the availability of highly effective methods of contraception, still many pregnancies are unwanted predisposing them to higher risk of mortality, often due to unsafe abortion. These unwanted pregnancies can be prevented using emergency contraceptive pills. This study aimed to investigate the knowledge, attitude and practice of emergency contraceptive pills and factors hindering its use among females of reproductive age group. Methods: Institution based cross-sectional study was conducted among 416 females of reproductive age group visiting urban heath centre of Rajbiraj, selected by purposive sampling technique. Data was collected using pretested semi-structured questionnaire after written informed consent. Descriptive & inferential statistics were used to analyze the data generated. Results: Out of 416 respondents, 34.6% were aware of emergency contraceptive pills and majority (56.9%) of them got to know it from Media. Among respondents who were aware of ECPs, 64% had good knowledge of it, 90% had positive attitude towards ECPs and 63% have used it earlier. A significant association was found between age, residence, educational level and occupational status with awareness of ECPs. Lack of awareness regarding ECPs has been hindering the usage of ECPs in emergencies to prevent unwanted pregnancies. Conclusions: Awareness and utilization of ECPs is low among females of terai region. Therefore awareness should be raised through formal education and communication by health personnel and through mass media which could provide reliable and accurate knowledge on ECPs.